A field test of the influence of pre-game imagery on basketball free throw shooting - Post, P. G.; Wrisberg, C. A.; Mullins, S. (Journal of Imagery Research in Sport and Physical Activity, 2010)
This field study examined the influence of a pre-game imagery intervention implemented by a high school coach on the free throw shooting performance of his girls' basketball team. The coach conducted a systematic guided imagery exercise prior to half of the team's games over the course of an entire season. The coach employed the intervention with the whole team using a reversal design similar to the replication-reversal design used in some single-subject research (Hume, Martin, Gonzalez, Cracklen, & Genthon, 1985). A 2 x 2 chi-square analysis was used to evaluate the observed and expected frequencies of made and missed free throw shots under the two conditions (imagery and no-imagery). The results revealed a significantly higher than expected number of free throws made in games preceded by the intervention (p < .001). Social validation questionnaires completed by 11 of the 16 players suggested that the players devoted significant attention to the intervention and that they perceived it to be effective.